Management of Recreation and Nature Based Tourism in European Forests - Prb̲stl, Ulrike.; Wirth, Veronika.; Elands, Birgit H. M.; Bell, Simon. (Springer Berlin Heidelberg : Imprint: Springer, 2010)
This book provides for the first time a Europe-wide overview on the state of the art of management of recreation and nature tourism in forests. It describes the current situation and conflicts in the different regions of Europe and provides solutions illustrated by good practise examples. It addresses traditions, differences and similarities in European forests as well as new tasks, goals and strategies. The final discussion provides a profound insight into future trends regarding forest recreation and nature based tourism.